Konsep Relasi Gender Sachiko Murata Dalam The Tao Of Islam - Sholikah Sholikah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2018)
Abstract, Gender equality is the subject of a controversial discussion. From it came various kinds of thinkers with their distinctive opinions. At first this problem arose due to the dissatisfaction of women as the second sex. Biologically good causes natural differences between men and women (nature), as well as cultures that contribute to the concept of gender, positioning women below men. Then feminists try to make theories that try to find similarities and equality between these two types of sex and gender. Therefore, the whole universe changes every moment, like a flowing river. From here it is important to review the concept of gender relations offered by Prof. Sochiko Murata as outlined in his work The Tao of Islam. Departing from the above problems, the problems that will be raised in this study are, 1) how is the concept of gender in general ?, 2) what is the biography of Sochiko Murata and what is the background of the book entitled The Tao of Islam? in The Tao Of Islam ?, and 4) what is the concept of gender relations offered by Sochiko Murata ?. Sochiko Murata in describing his thoughts on gender relations oriented to the Chinese cosmological concept with the famous philosophy yin and yang. This concept also applies to gender relations where each gender has yin and its own. Yin which is synonymous with feminine and which is synonymous with masculine must collaborate in a balanced manner according to its functions and roles to produce harmony. The gender relations he tried to express were not only limited to the human sphere, but also the entire cosmos, namely the macrocosm (nature), microcosm (human), and metacosmos (God).